Thermal production of astrophobic axions - Marcin Badziak; Keisuke Harigaya; Michał Łukawski; Robert Ziegler (Journal of High Energy Physics, 2024)
Abstract Hot axions are produced in the early Universe via their interactions with Standard Model particles, contributing to dark radiation commonly parameterized as ∆N eff. In standard QCD axion benchmark models, this contribution to ∆N eff is negligible after taking into account astrophysical limits such as the SN1987A bound. We therefore compute the axion contribution to ∆N eff in so-called astrophobic axion models characterized by strongly suppressed axion couplings to nucleons and electrons, in which astrophysical constraints are relaxed and ∆N eff may be sizable. We also construct new astrophobic models in which axion couplings to photons and/or muons are suppressed as well, allowing for axion masses as large as few eV. Most astrophobic models are within the reach of CMB-S4, while some allow for ∆N eff as large as the current upper bound from Planck and thus will be probed by the Simons Observatory. The majority of astrophobic axion models predicting large ∆N eff is also within the reach of IAXO or even BabyIAXO.